2014
DOI: 10.1186/1742-4755-11-80
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Group B Streptococus recto-vaginal colonization and antimicrobial susceptibility pattern in pregnant mothers at two hospitals of Addis Ababa, Ethiopia

Abstract: BackgroundGroup B streptococcus (GBS) has been implicated in adverse pregnancy outcomes. GBS recto-vaginal colonization rates significantly vary among different communities and geographic locations. Limited data is available on the prevalence and effects of GBS recto-vaginal colonization among pregnant mothers in developing countries like Ethiopia.ObjectiveTo assess the prevalence of GBS recto-vaginal colonization among near term pregnant mothers and the antimicrobial susceptibility pattern of the isolates.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 9 publications
5
37
8
Order By: Relevance
“…A high rate of GBS colonization is often obtained if women are followed up for a certain period and both the rectal and vaginal sites are investigated which was the case in the current study. GBS colonization rates are known to vary with different geographical localities and different communities [2,16]. This is attributed to variation in socio-economic factors and sampling techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high rate of GBS colonization is often obtained if women are followed up for a certain period and both the rectal and vaginal sites are investigated which was the case in the current study. GBS colonization rates are known to vary with different geographical localities and different communities [2,16]. This is attributed to variation in socio-economic factors and sampling techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to variation in socio-economic factors and sampling techniques. Cultural, ethnic and genetic factors play a role in the variation of the rates of infection with GBS [2,19,20]. Lower rates are attributed to false negative culture due to inadequate swabbing technique or poor handling, specimen storage conditions, and prolonged transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the timing of specimen collection in pregnancy, selective culture methods, and study sample size did not explain the heterogeneity [10]. In Ethiopia, the study by Muhammed et al showed that GBS colonization rates (20.6 %) were higher than reported by Lakew et al (7.2 %) [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, few studies have been conducted on GBS [11, 12, 15–17] although infant mortality is high in this population. Until today, there are no public health policies or strategies in Ethiopia aimed at the reduction of GBS neonatal infection.…”
Section: Introductionmentioning
confidence: 99%